Breaking barriers: A Pediatrician's perspective on enhancing early diagnosis of developmental dysplasia of the hip - Shang-Po Shen; Chien-Chung Kuo; Hao-Wen Cheng; Ming-Luen Tsai; Chun-Yi Yang; Chien-Lin Lin; Hung-Chih Lin; Yin-Ting Chen (Journal of the Formosan Medical Association)
Background: Detecting Developmental Dysplasia of the Hip (DDH) early is vital for normal hip development (90% success). Taiwan's free baby check-ups target early diagnosis through neonatal exams and selective sonography. The study assesses a program's impact on high-risk patient selection and early DDH diagnosis. Methods: In May 2022, a Quality Improvement (QI) program for Developmental Dysplasia of the Hip (DDH) was initiated, involving neonatologists, orthopedics, and administrators. A guideline-based bundle was developed, focusing on early detection. Pediatricians enrolled high-risk infants, and qualified neonatologists conducted selective hip sonography, confirmed by orthopedics. The program emphasized parental education. QI indicators monitored screening efficiency and DDH incidence, with early diagnosis defined within 6 months. The study assesses DDH incidence pre- and post-bundle implementation. Results: Between 2012 and 2021, the average DDH diagnosis rate was 0.48/1000, with a 50% early diagnosis rate. After introducing a new bundle in May 2022, the diagnosis rate increased to 3.5/1000, and the early diagnosis rate reached 69%. Pre-bundle, 22 cases (0.78%, 22/2843) received sonography, 54.5% before 4 months. Post-bundle, 942 cases (33.4%, 942/2820) underwent sonography, 96.4% before 4 months. The study highlights a significant post-bundle increase in screened infants, contributing to a higher early diagnosis rate. Conclusion: The results of the study suggest that the health promotion policy in the single hospital is associated with an increase in early diagnosis of DDH. Subsequently decline of incidences of major surgery for DDH is to be expected. It has raised issues of the effectiveness of baby hip screening.